Organizational Culture and Citizenship Behavior in Community-Based Ecotourism: The Case of CMC Tiga Warna Malang - Krisna Veda Aryaputra; Risfandini, Andini; Sumarsono, Tanto Gatot; Estocada, Donato Z. (Proceedings of International Conference of Graduate School on Sustainability, 2026)
This study examines the influence of organizational culture on Organizational Citizenship Behavior (OCB) among employees of Clungup Mangrove Conservation (CMC) Tiga Warna Ecotourism in Malang, Indonesia. As a community-based ecotourism initiative, CMC Tiga Warna integrates environmental conservation with sustainable tourism practices, making employee behavior a key factor in maintaining its success. Using a saturated sampling method, all 45 employees—including tour guides, field technicians, and management staff—were surveyed through questionnaires and supported by direct observation. The findings reveal that organizational culture has a significant positive effect on OCB (β = 0.342, p < 0.05). A strong organizational culture emphasizing teamwork, shared responsibility, and commitment to environmental values encourages employees to voluntarily engage in behaviors that go beyond their formal job roles. These results highlight the importance of fostering a cohesive and value-driven organizational environment to strengthen proactive and cooperative behaviors among employees. Strengthening internal communication, leadership example, and recognition of positive contributions are recommended to sustain and enhance OCB within the organization.